National Annual Report 2007. IICA's contribution to agriculture and the development of the rural communities in Grenada - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
The actions of the Inter-American Institute for Cooperation on Agriculture (IICA) are presented, and its purposes are to promote and support the efforts of its member states to achieve agricultural development and the well-being of rural areas. IICA's technical cooperation is presented, which emphasizes operations efficiency, prudent financial management, better use of human resources, expansion links with international strategic partners and a new relationship with Member States based on participation, transparency and accountability, considering the repositioning needs of agriculture and rural life, promoting trade and the competitiveness of agribusiness, strengthening agricultural health and food safety systems, promoting Sustainable Resource Management Natural and Environment, strengthening of rural communities from a territorial approach, and introduction of technology and innovation for the modernization of agriculture and rural life.